Dynamic Study of the General Carrera Median System Considering the Incorporation of a Bess - Chavez-Orostica, H; Fuentes-Parra, C; Riquelme-Vera, E; Quiroz-Moreno, J; Gonzalez-Pincheira, L (Institute of Electrical and Electronics Engineers Inc., 2023)
Within the context of transitioning towards a sustainable energy matrix, the incorporation of renewable energy sources into Power Systems (PS) has been rapidly increasing. However, this shift leads to a reduction in system inertia, which could potentially cause stability issues. To enhance operational stability, PS can implement Battery Energy Storage Systems (BESS). Nonetheless, it is crucial to conduct dynamic studies prior to their deployment to ensure optimal system performance. In this context, this paper presents a dynamic study of the General Carrera medium-scale power system in Chile, considering the integration of a BESS. The study, successfully conducted using the Power Factory tool by Digsilent, included the simulation of five unexpected generation disconnection scenarios and five short circuits for each of the seven generation buses, totaling 280 case studies. The objective of these simulations was to verify both angle and frequency stability and to define the optimal location for the BESS. The results obtained conclude that placing the BESS at the Kosten bus offers the highest number of scenarios with favorable dynamic performances, thus contributing to improving the stability of the General Carrera medium-scale system amidst the high inclusion of renewable energies. Therefore, this study provides a valuable framework for the future planning and operation of this system within the context of the energy transition. © 2023 IEEE.
Keywords: BESS Integration; Dynamic Stability; Renewable Energy